Keragaman Genetik Klon Kakao Lokal Sulawesi Tenggara Berdasarkan Marka SSR dan Karakter Morfologi - Nur Kholilatul Izzah; Budi Martono; Baharuddin Baharuddin; Edi Wardiana (Jurnal Tanaman Industri dan Penyegar, 2018)
Molecular and morphological characterization of cacao clones obtained from exploration in Southeast Sulawesi is very important to know their superiority and genetic relationships. Analysis of genetic diversity using molecular markers is also useful for detecting duplication found among collected clones. The research aimed to determine the genetic diversity of local cacao clones derived from Southeast Sulawesi based on SSR markers and morphological characters. The research was conducted at Cacao Research Sub-Station, Lebojaya Village, Konda Subdistrict, South Konawe Regency, Southeast Sulawesi, and Integrated Laboratory of Indonesian Industrial and Beverage Crops Research Institute Sukabumi, and Molecular Biology Laboratory of Indonesian Center for Agricultural Biotechnology and Genetic Resources Research and Development Bogor, from April to November 2015. Genetic diversity analysis was performed on 21 cacao clones covering 19 local clones and 2 national varieties using 22 SSR markers. The molecular characterization results showed that 11 markers are polymorphic, and subsequently used to group cacao clones using NTSYS program. The grouping results divided the cacao clones into 4 main groups at 0.46 genetic similarity values. Based on genetic distance values >0.7, 8 combinations of cacao clones can be selected as parental clones with the expectation to increase the effect of heterosis on progeny. On the other hand, result of morphological characterization generally indicated the diversity between the four cacao groups. Based on molecular and morphological characterization, it can be seen that cacao clones derived from Southeast Sulawesi have a high diversity and can be utilized in the development program of new improved varieties.